Molecular identification of the medicinal and edible plant Spatholobus suberectus Dunn and its counterfeits and adulterants based on rbcL barcode - Jiawen Wu; Yunfeng Huang; Renchuan Hu; Qimin Hu; Chuangui Xu; Kedao Lai; Ziyi Zhao (CyTA - Journal of Food)
The study aimed to compare and analyze the ribulose-1, 5-bisphosphate carboxylase (rbcL) sequences of Spatholobus suberectus Dunn and its adulterants and to explore whether rbcL could be used as the DNA barcode to effectively identify them. The obtained sample rbcL sequences were compared with those in the NCBI database, and the alignment results were consistent with the morphological identification results. The phylogenetic tree shows that the rbcL sequence of S. suberectus clusters as a distinct branch, clearly distinguishing it from other species. The K2P genetic distance analysis reveals that the average intra-species genetic distance of S. suberectus is smaller than the average inter-species genetic distance between S. suberectus and other species, indicating a clear genetic divergence between S. suberectus and other species based on the rbcL sequence. In conclusion, the rbcL barcode is an efficient and accurate DNA barcode for distinguishing S. suberectus from its adulterants.